Electron temperature measurements with a hairpin resonator probe in a pulsed low pressure capacitively coupled plasma. (17th June 2021) - Peterson, D; Xiao, Y; Ford, K; Kraus, P; Shannon, S
Abstract: Electron temperature is measured from time resolved hairpin resonator probe measurements in a pulsed capacitively coupled argon plasma at 400 mTorr. Effective collision frequency is related to the electron energy distribution via the effective conductivity and closes a system of equations that allow electron temperature to be determined. Results generally show good agreement with expected behavior and unfiltered time-resolved optical emission measurements.